Przekształcenia lokalnego potencjału rozwojowego we Wrocławskim Obszarze Metropolitarnym na przełomie wieków - Rogowska, Małgorzata; Potoczna, Iwona; Mempel-Śnieżyk, Anna (Changes in Local Development Potential in Wroclaw Metropolitan Area at the Beginning of the 21st Century, 2007)
The main aim of this article is to describe transformations in local development potential in Wroclaw Metropolitan Area. In the last decade of the 20lh century one can observe changes in special structures of local and regional units. Metropolises and their closest areas are becoming more important in regional development.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 328-339